DST no âmbito da relação estável : análise cultural com base na perspectiva da mulher - Sousa, Leilane Barbosa de (2007)
Risk groups for sexually transmitted diseases (STD) were defined with the support of the advent of the HIV/aids discovery. They are centered in homosexuals and sex professionals, so the people who were not included in these groups did not consider themselves vulnerable to STD. The non-consideration of the risk caused an inversion in the number of STD cases in specific populations. The numbers reveal, for example, that the reason between the HIV occurrence among men and women tends to decrease and that the transmission among heterosexuals is already higher than among homosexuals. In face of this situation, heterosexual women started to be considered a risk group, including the ones with stable union. After the diagnosis, the woman may experience a situation of conflict with her partner when trying to discover the origin of contamination. When this problem was detected, it was perceived the necessity to investigate the STD contamination in the couple’s dynamics, with the objective of identifying cultural factors which are determinant for the risk of contamination by STD and understand the meaning of STD contamination for the couple. It was considered necessary the execution of an ethnographical research, based on Theory of Cultural Care to accomplish the proposed objectives. The study was developed in the Center of Family Development (CEDEFAM) and in seven women’s family context for nine months. It was possible to identify the interaction of information about STD in professional and popular (general) health systems, so that the gap in relation to knowledge and awareness about the risk seems to emerge from cultural and gender questions which are transmitted, shared and ingrained in society. It was also ascertained that the STD diagnosis influences on women’s sexual behavior. They start to rediscover their body and to develop signs of care about the couple’s sexual and reproductive health. On the other hand, it was verified that men seem to behave as having a secondary role in the process and still consider the problem a feminine one. As a conclusion, it was noticed the importance of the approach of culture in Health Education actions for the promotion of couple’s sexual and reproductive health. We believe that, with the support of culturally directed Health Education strategies, results with positive impact can be reached in the assimilation of risks and rupture of the STD transmission chain.